On-site salt iodine detector (OSID) kit: An alternative tool for salt iodization monitoring - Mohd Azerulazree Jamilan; Nurul Aznyda Norizan; Ahmad Ali Zainuddin; Noor ul-Aziha Muhammad; Filza Noor Asari; Aswir Abd Rashed; Mohd Fairulnizal Md Noh (MethodsX, 2025)
Iodine fortification of cooking salt prevents iodine deficiency, but current monitoring methods are labor-intensive. Here, we validated the On-Site Salt Iodine Detector (OSID) kit as a reliable tool for salt iodine analysis. The OSID kit was optimized for a salt weight (346.1 ± 4.9 mg) and volume of solution D (39.1 ± 1.2 µL), enabling 100 sample analyses. The validation was by its linearity (10.0–50.0 mg/Kg, R2 = 0.9956) with limit of detection (LOD, 3.6 mg/Kg), method recovery (89.5 %-99.4 %), intra-assay imprecision (coefficient of variation, CV 5.7 %), inter-assay imprecision (CV 7.0 %) and inter-operator imprecision (CV 6.1 %). A 30.0 mg/Kg iodate and sample S4 used as quality control (QC) for ten days monitoring which resulted within the range of mean±2×standard deviation (SD) (27.2 ± 2.4 mg/Kg and 21.6 ± 5.3 mg/Kg, respectively). The OSID kit showed strong agreement in a Blant-Altman plot when compared with UHPLC (60 salt samples) indicating a reliable and cost-effective alternative for salt iodine monitoring. • The optimization of salt weight and volume of solution D allows 100 analyses per kit. • The OSID kit imprecision validation of <10 % demonstrate excellent precision and reliability of the method. • The result comparison between the OSID kit and the UHPLC reference method suggest a strong agreement in a Blant-Altman plot.